Ultrasonic echo method in detection of breast calcifications. Transient analysis - FILIPCZYŃSKI, Leszek; KUJAWSKA, Tamara; ŁYPACEWICZ, Grażyna (Archives of Acoustics, 1986)
The detestability of calcifications in women breast by means of the ultrasonic echo method was estimated on the basis of the transient analysis of the ultrasonic pulse reflection. Two calcification models in the form of a rigid and an elastic sphere were considered. Echoes obtained at tissue inhomogeneities form an interference back-ground which masks echoes from small calcifications. The level of the tissue interference background was determined on the basis of measurements in 100 femal breasts and it was shown that the obtained experimental results are probable from the theoretical point of view. As the result of the performed analysis and experiments the author concluded that microcalcifications are not detectable by the ultrasonic echo method. The radii of calcifications which can be found at the frequency of 5 MHz are equal to 0.6 mm or 1.6 mm depending on the maximum sampling error assumed for a single measurement of the tissue interference background.